Soils of Volcanic Regions in Europe - Arnalds, Ólafur; Bartoli, Francois; Buurman, Peter; Oskarsson, Hlynur; Stoops, Georges; Garcia-Rodeja, Eduardo (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Soils of volcanic areas often exhibit unique properties differentiating them from other soils on Earth. This publication compiles information gained by an EU research network over six years of research on European volcanic soils. The book gives comprehensive coverage of soils in volcanic regions within Europe, dealing with most aspects of modern day soil science. New methodology is introduced and the synthesis of the research casts a new light on soils with andic soil properties. It covers a range of issues such as mineralogy, chemistry, physics, biology, soil genesis, classification, land use and pollution.